2012 14th Symposium on Virtual and Augmented Reality 2012
DOI: 10.1109/svr.2012.28
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study on the Implementation of the 3C Collaboration Model in Virtual Environments

Abstract: Throughout the years many studies have explored the potential of Virtual Reality (VR) technologies to support collaborative work. However few studies looked into CSCW (Computer Supported Cooperative Work) collaboration models that could help VR systems improve the support for collaborative tasks. This paper analyzes the applicability of the 3C collaboration model as a methodology to model and define collaborative tools in the development of a collaborative virtual reality application. A case study will be pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 16 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…In the same year, Medeiros et al (2012) analyzed the applicability of the 3C collaboration model as a methodology to model and define collaborative tools in the development of a collaborative virtual reality application. The presented case study illustrated the selection and evaluation of different tools that aim to support the actions of communication, cooperation and coordination between users that interact in a virtual environment.…”
Section: Multi-user and Distributed Xrmentioning
confidence: 99%
“…In the same year, Medeiros et al (2012) analyzed the applicability of the 3C collaboration model as a methodology to model and define collaborative tools in the development of a collaborative virtual reality application. The presented case study illustrated the selection and evaluation of different tools that aim to support the actions of communication, cooperation and coordination between users that interact in a virtual environment.…”
Section: Multi-user and Distributed Xrmentioning
confidence: 99%
“…The studies conducted by the researchers [13] [14] [15] showed the interest to have a social development environment which unifies the concepts of social network and the concept of collaborative environment applying the 3C (cooperation, communication and coordination) to maintain the motivation of the various members of the development team.…”
Section: B Collaborative Development Environmentmentioning
confidence: 99%
“…Manuscript submitted to ACM Previous works on collaboration between immersed and non-immersed users were designed for constrained scenarios such as specially designed games [14,15,38]. Our approach targets generic asymmetric collaboration/presentation scenarios where users have different affordances and tasks, but need to be able to share their experience, sense of immersion, and communicate about the environment (through the use of pointing gestures).…”
Section: Introductionmentioning
confidence: 99%